High-throughput sequencing reveals the structure and metabolic resilience of desert microbiome confronting climate change - Mousa, Walaa K.; Abu-Izneid, Tareq; Salah-Tantawy, Ahmed (Frontiers in Plant Science, 2024)
Introduction Desert ecosystems harbor a unique microbial diversity that is crucial for ecological stability and biogeochemical cycles. An in-depth understanding of the biodiversity, compositions, and functions of these microbial communities is imperative to navigate global changes and confront potential threats and opportunities applicable to agricultural ecosystems amid climate change. Methods This study explores microbial communities in the rhizosphere and endosphere of desert plants native to the Arabian Peninsula using next-generation sequencing of the 16S rRNA gene (V3-V4 hypervariable region). Results Our results reveal that each microbial community has a diverse and unique microbial composition. Based on alpha and beta diversity indices, the rhizosphere microbiome is significantly diverse and richer in microbial taxa compared to the endosphere. The data reveals a shift towards fast-growing microbes with active metabolism, involvement in nutrient cycling, nitrogen fixation, and defense pathways. Our data reveals the presence of habitat-specific microbial communities in the desert, highlighting their remarkable resilience and adaptability to extreme environmental conditions. Notably, we observed the existence of radiation-resistant microbes such as Deinococcus radiotolerans, Kocuria sp., and Rubrobacter radiotolerans which can tolerate high levels of ionizing radiation. Additionally, examples of microbes exhibiting tolerance to challenging conditions include Nocardioides halotolerans, thriving in high-salinity environments, and hyperthermophilic microbes such as Quasibacillus thermotolerans. Moreover, functional analysis reveals enrichment in chaperon biosynthesis pathways associated with correct protein folding under heat stress conditions. Discussion Our research sheds light on the unique diversity of desert microbes and underscores their potential applications to increase the resilience of agriculture ecosystems, offering a promising strategy to fortify crops against the challenges posed by climate change, ultimately supporting sustainable food production for our ever-expanding global population.